Analisis Struktur Bagian Atas (Upper Structure) dalam Ilmu Konstruksi Bangunan Studi kasus : Pekerjaan Tiang Kolom Pada Proyek Pembangunan Gedung Serbaguna GBKP Marendal - Mekatani Kabupaten Deli Serdang. - Ronald Rezeki Tarigan; Yohanes Sibagariang (Universitas Quality, 2021)
Column in principle is a rigid frame system which in case of loading will be accepted by all systems and jointly support each other. The term column is used in civil engineering to define a building construction that functions as a support for the building that accepts the load and transmits the load of the building in all directions with a strong enough carrying capacity. The building column is also a compressive element that supports / holds the beam + floor that carries the loads on the floor. So this column is very meaningful for the structure. If the column collapses, the whole building collapses. Coulom, Structure and Civil Building Contruction.